DIVERSITY OF MICROBES IN SOIL AGGREGATE FRACTIONS UNDER DIFFERENT LAND-USE IN NORTHERN GUINEA SAVANNA, NIGERIA - Lawal, Halima Mohammed; Salifu, U. M.; Amapu, I. Y.; Atta, H. I. (FUDMA JOURNAL OF SCIENCES, 2020)
Microorganisms play vital role in keeping soil healthy. Bacteria, Fungi and Actinobacteria are active in degrading soil organic matter which improves soil ecosystem functioning. There exists a dearth of information on the influence of land-use on diversity of microbes in different soil aggregate sizes in Northern Guinea Savanna of Nigeria. This study assessed the diversity of soil microbes under six different land-use practices namely forest, fallow, pasture legume, pasture cereal, date palm plantation and continuous cultivated. In each land-use soil samples were collected at two depths (0-5 cm and 5-20 cm). The soil samples were divided into two parts, one part was left as collected from the field sites (bulk soil) and the other part was separated into three aggregate fractions (>250 µm, >53 µm and <53 µm). Bacteria, Fungi and Actinobacteria were cultured, isolated and identified, and some soil chemical properties were determined. Colony forming units per gram of soil (CFU/g soil) was computed for the soil microbes. Results revealed that Bacteria is the predominant soil microbe followed by Actinobacteria and then Fungi in all the land-uses. Bacteria population ranged from 1.49x107to 8.65x107CFU/g soil, Actinobacteria population ranged from 9.32x105 to 5.85x106 CFU/g soil and Fungi population ranged between 6.75x104 and 4.21x105 CFU/g soil. Higher microbial population were observed in forest soil than soils of the other land-uses. Continuously cultivated land had the least microbial population. Silt + clay soil fraction had significantly higher bacteria while the bulk soil was significantly richer in fungal population.